Cuidado de enfermagem em grupo à família de crianças/adolescentes com transplantes cardíacos - Ribeiro, Silvania Braga (2012)
The familial relationship frequently are very hard to be understood, then to increase our perception it is important to know the concept and family structure, roles and how the members organize themselves and interact with each other. We aim to develop strategy for nursing care in the family group. In a qualitative approach, through the methodological framework of Loomis (1979). The group approach adopted to the family and child / adolescent cardiac transplant in a tertiary hospital in Fortaleza. The group process is divided by three phases: planning (goals), intervention (structure and process) and evaluation (results), as the main objective of the group were support / learning. The theoretical framework was driven using as the genogram assessment, by model of Calgary Family Assessment (MCAF). The volunteers selected to the study were 15 relatives of children / adolescents who underwent heart transplantation. However through the inclusion and exclusion criteria, remained eight relatives to folow up. The data collection was performed from June to September (2012). The data used for analysis were: descriptive report of the session (audio and photos recorded) and speeches of the volunteers in interview, using the construction of the genogram. At each session, we identified the main therapeutic factors as: cohesion, catharsis, offering information, altruism, universality and instillation of hope that integrate the resolution process for their specific goals. The aims were achieved since we developed the strategy of the nursing care to the family group, using the reference group stages (group development), focusing on the proposed objective: support and learning. Furthermore the group and coordinator evaluation was assessed as being effective, since we could verify the phases from the perspective of the theory that constitute the curative factors in a group of health care that were identified in each session. To accomplish this nursing group practice in the hospital service, takes time and dedication to provide the nurse, that very often overwhelmed in service. We suggest that pediatric hospitals encourage their nurses to perform further research on nursing care in the family group and the child, as well as the nurse will be prepared and scientifically based practice, in order to provide satisfactory results to the institution.